Beta diversity patterns reveal positive effects of farmland abandonment on moth communities - Dantas de Miranda, Murilo (2019)
Farmland abandonment and the accompanying natural succession are largely perceived as unwanted amongst many European conservationists due to alleged negative effects on biodiversity levels. Here, we test this assumption by analysing alpha, beta and gamma diversity patterns of macro-moth communities in habitats on an ecological succession gradient, from extensively managed meadows to scrub-encroached and wooded sites. Macro-moths were light-trapped at 84 fixed circular sampling sites arranged in a semi-nested design within the National Park of Peneda-Gerês, NW-Portugal. In total, we sampled 22825 individuals belonging to 378 species. Alpha, beta and gamma diversity patterns suggest that farmland abandonment is likely to positively affect both overall macro-moth diversity and forest macro-moth diversity, and to negatively affect species diversity of non-forest macro-moth species. Our results also show that spatial habitat heterogeneity is important to maintain gamma diversity of macromoths, especially for rare non-forest species and habitat specialists